If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8m + 2 + 7m = 2(4m + -5) + 8(-6 + -1m) Reorder the terms: 2 + 8m + 7m = 2(4m + -5) + 8(-6 + -1m) Combine like terms: 8m + 7m = 15m 2 + 15m = 2(4m + -5) + 8(-6 + -1m) Reorder the terms: 2 + 15m = 2(-5 + 4m) + 8(-6 + -1m) 2 + 15m = (-5 * 2 + 4m * 2) + 8(-6 + -1m) 2 + 15m = (-10 + 8m) + 8(-6 + -1m) 2 + 15m = -10 + 8m + (-6 * 8 + -1m * 8) 2 + 15m = -10 + 8m + (-48 + -8m) Reorder the terms: 2 + 15m = -10 + -48 + 8m + -8m Combine like terms: -10 + -48 = -58 2 + 15m = -58 + 8m + -8m Combine like terms: 8m + -8m = 0 2 + 15m = -58 + 0 2 + 15m = -58 Solving 2 + 15m = -58 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 15m = -58 + -2 Combine like terms: 2 + -2 = 0 0 + 15m = -58 + -2 15m = -58 + -2 Combine like terms: -58 + -2 = -60 15m = -60 Divide each side by '15'. m = -4 Simplifying m = -4
| 7=-x+4 | | 6x-2y=-4 | | 4x^2+32x=132 | | -6(1+3x)=-2(-6+6x)+3x | | 2x+y=11 | | 2x^3+32x=16x^2 | | 7x+6y+5=0 | | -2x+7=5-(4x+7) | | -5a+6(a+2)=2(a+1)-3 | | 2x+2y=16 | | 8x-11=8(x-2) | | w^4-4=3 | | 2(3+5x)-5=61 | | 7(4+5x)+8= | | -(3+4p)+2p=-(5p+3) | | -4(7-6n)+2= | | 4(c+5)11c=110 | | .9(x+30)+.9x=108 | | -2(4-8b)=-3(1-7b) | | 96=-5x-5x+6 | | 4(2x-2)=24 | | (-3x-8)=(-7x-3) | | x-0.77777777777=1-7 | | -5(x-1)-x= | | -1-5x-3x=-1 | | 3y+19=4y+5 | | 1-x(x-3)=4x-1 | | 3x+0.375=4x-0.375 | | 3x+0.375=4-0.375 | | -112=-5x-7x+8 | | 6x+9=-57 | | 3x+x=144 |